The Edinburgh companion to modernism, myth and religion - Hobson, Suzanne; Radford, Andrew, 1972- (Edinburgh : Edinburgh University Press, 2023)
"Until fairly recently, the 'Authorised Version' of cultural modernism stated that the secularising trends of liberal modernity -- and the resultant emphasis on irony, parody and dissolution in modernist artforms -- had pushed religion to the edges of early twentieth-century culture. This Companion complicates this understanding by furnishing students and academic researchers with more nuanced and probing assessments of the intersections and tensions between religion, myth and creativity during this half century of geopolitical ferment. It addresses the variety and specificity of modernist spiritualities as well as the intricately textured and shifting standpoints that modernist figures have occupied in relation to theological traditions, practices, creeds and institutions. What emerges is a multi-textured account of modernism's deep-rooted concern with the historical and established forms of religion, as well as new engagements with 'occulture' and indigenous traditions. In short, the Companion supplies a lively and original exploration of the aesthetic, publishing, technological and philosophical trends that shape debates about spirituality, community and self from the 1890s to the 1940s and beyond"--
Ezra Pound versus T.S. Eliot on Christianity, apocalypse and myth, 1934-1945 / Erik Tonning -- Virginia Woolf and Christianity / Jane de Gay -- H.D. and spirituality / Lara Vetter -- D.H. Lawrence's dark god / Luke Ferretter -- Harlem's Bible stories : Christianity and the new Negro movement / Steve Pinkerton -- The Jewish East End and modernism / Alex Grafen -- Troubled : Reverse theodicy in Ward, Eliot and Baldwin / Douglas Mao -- Modernism, secular hope and the posthumous trace / David Sherman -- C.K. Ogden, I.A. Richards and "word magic" : Rethinking the relation of language to myth / Leigh Wilson -- Jean Toomer and the face of the real : Between sacred presence and disenchanting violence / Matthew Mutter -- Modernism and political theology / Charles Andrews -- Virginia Woolf's agnostic, visionary mysticism : Approaching and retreating from the sacred / Gabrielle McIntire -- Modernism, abstraction and spirituality : Barbara Hepworth and Hilma af Klint / Lorraine Sim -- Modernism and the hymn / Sean Pryor -- William James, mysticism and the modernist epiphany / Graham H. Jensen -- Modernist mythopoeia / Scott Freer -- Yeats's sacred grove / Seán Hewitt -- The modernist grail quest / Andrew Radford -- The burial of the dead in Mann's The Magic Mountain / Pericles Lewis -- The modernist afterlives of theosophy / Allan Kilner-Johnson -- Rebecca West, modern spiritualism and the problem of other minds / Jennifer Spitzer -- "What God hath joined, let no pragmatist put asunder" : May Sinclair's philosophical idealism as surrogate religion / Rebecca Bowler -- Sacred ground : Orthodoxy, poetry and religious change / Jamie Callison -- Liminal spaces and spiritual practice in Naomi Mitchison, Keri Hulme and Lorna Goodison / Elizabeth Anderson -- Finnegans Wake, modernist time machines and re-enchanted time / Gregory Erickson -- Global seekers in The Quest : A case study of an occult periodical's worldly religion / Mimi Winick -- "A miserable attenuation" : T.S. Eliot, Rabindranath Tagore and Irving Babbitt / Mafruha Mohua -- "Part heathen, part Christian" : Recording transitions and amalgamations of belief systems in Constantine Cavafy's poetry / Sanja Bahun -- "It was really rather fine to be suffering" : Radclyffe Hall at the queer intersection of masochism and martyrdom / Jennifer Mitchell -- The Byzantine modernism of Djuna Barnes / Christos Hadjiyiannis -- "Mixed sex cases among goats" : The modernist sublime / Matte Robinson and Lisa Banks.
Includes bibliographical references and index.
Suzanne Hobson is Reader in 20th Century Literature in the English Department at Queen Mary University of London. Andrew Radford is Senior Lecturer in Critical Studies at the University of Glasgow.
Print version record.
JSTOR
Keywords: Modernism (Literature) -- Religious aspects; Modernisme (Littérature) -- Aspect religieux; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Literature: history & criticism; Literary studies: general; Literary studies: poetry & poets; Literary studies: fiction, novelists & prose writers; Literary reference works; Literature; Literary criticism; Literary criticism; Critiques littéraires.